UJI AKTIVITAS ANTIOKSIDAN FRAKSI DIETIL ETER DAUN BERUWAS LAUT (Scaevola taccada (Gaertn.) Roxb.) PADA TIKUS (Rattus norvegicus) YANG DIINDUKSI ALOKSAN DENGAN PARAMETER MDA - Sukmawati Sukmawati; Rahmawati Rahmawati; Firdaus Firdaus (Fakultas Farmasi UMI, 2013)
The research on the antioxidant activity test of dietil eter fraction from beruwas laut leaf (Scaevola taccada (Gaertn.) Roxb.) on diabetic rats (Rattus norvegicus) with MDA indicator. This research was aimed to prove antioxidant activity of dietil eter fraction of beruwas laut (Scaevola taccada (Gaertn.) Roxb.) on diabetic rats (Rattus norvegicus) with MDA indicator. This research use 6 male rats were divided into 2 groups. Each groups consists of 3 male rats. All of rats on diabetic condition by alloxan induced 110 mg/kg BB intraperitoneal injection. The control group has been given Na CMC 1%, the fraction 3% group has been given dietil eter fraction 3%. Administration were orally until 7 days. At the end of research, all of rats were taked their blood for determined of absorbance at spektrofotometer 532 nm wave length. The result of the research showed that dietil eter fraction 3% can decreased MDA absorbance of diabetic rats (Rattus norvegicus). Key Word : Antioxidant, Scaevola taccada, MDA, Rattus norvegicus